1988
DOI: 10.1007/bf01128970
|View full text |Cite
|
Sign up to set email alerts
|

Cell surface effects of human immunodeficiency virus

Abstract: Cell killing by human immunodeficiency virus (HIV) is thought to contribute to many of the defects of the acquired immunodeficiency syndrome (AIDS). Two types of cytopathology are observed in HIV-infected cultured cells: cell-cell fusion and killing of single cells. Both killing processes appear to involve cell surface effects of HIV. A model is proposed for the HIV-mediated cell surface processes which could result in cell-cell fusion and single cell killing. The purpose of this model is to define the potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

1990
1990
1998
1998

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 70 publications
1
7
0
Order By: Relevance
“…Thus, cell volume is regulated principally by ion transport systems, such the cardiac glycoside-sensitive Na ϩ /K ϩ ATPase (sodium pump), the loop diuretic-sensitive Na ϩ /K ϩ /2Cl Ϫ cotransporter, and active and passive ion channels (1a, 31, 32). Alterations in membrane ion permeability or transport have been implicated in induction of HIV-mediated cytopathology and could contribute to loss of volume control (13,21,25,39,40). The current studies extend this work and indicate that HIV-induced cytopathology temporally correlates with alterations in intracellular Na ϩ and K ϩ concentrations ([Na ϩ ] i and [K ϩ ] i ).…”
supporting
confidence: 71%
See 1 more Smart Citation
“…Thus, cell volume is regulated principally by ion transport systems, such the cardiac glycoside-sensitive Na ϩ /K ϩ ATPase (sodium pump), the loop diuretic-sensitive Na ϩ /K ϩ /2Cl Ϫ cotransporter, and active and passive ion channels (1a, 31, 32). Alterations in membrane ion permeability or transport have been implicated in induction of HIV-mediated cytopathology and could contribute to loss of volume control (13,21,25,39,40). The current studies extend this work and indicate that HIV-induced cytopathology temporally correlates with alterations in intracellular Na ϩ and K ϩ concentrations ([Na ϩ ] i and [K ϩ ] i ).…”
supporting
confidence: 71%
“…The image produced was stored on an optical disk or printed by using a photographic-quality printer. (20,21,25,37). To investigate the mechanisms for the observed cytopathology, intracellular concentrations of K ϩ and Na ϩ , two ions known to be critical in the control of cell volume (1a, 49), were measured in cells infected by HIV.…”
Section: True-color-real-time Microscopic Analysis Of Hiv-infected Anmentioning
confidence: 99%
“…The mechanism by which HIV reduces pH i in T-lymphoblastoid cells is not established in the current study. Prior studies indicated that HIV infection increases [Na ϩ i ] (20,54). Homeostatic mechanisms that control pH i may respond to the increase in [Na ϩ ] i by reducing the activity of the Na ϩ /H ϩ exchange system.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, syncytium formation is the consequence of increased cell fusion, an activity related to the virus glycoprotein gp41 (7,25,42,44). The mechanisms of individual cell killing are more complex; several HIV-1 gene products, such as gp41 and Vpu, could participate in this process by inducing plasma membrane modifications (16,28). Thus, permeability of membranes to a number of compounds, including ions, increases in HIV-1infected T cells, suggesting the appearance of hydrophilic pores in the membrane (40) as occurs in other virus-cell systems (10).…”
mentioning
confidence: 99%